Efficient solution route to transparent ZnO semiconductor films using colloidal nanocrystals*. Issue 3 (1st September 2016) - Suehiro, Satoshi; Horita, Keisuke; Pramata, Azzah Dyah; Yuasa, Masayoshi; Ishiwata, Yoichi; Shimanoe, Kengo; Kida, Tetsuya
Abstract: ZnO nanocrystals (NCs) were synthesized by heating Zn (II) acetylacetonate in oleic acid/oleylamine in the presence of 1, 2-hexadecanediol at 220 °C. Transmission electron microscopy (TEM) and dynamic light scattering (DLS) measurements revealed the formation of monodispersed ZnO NCs of ca. 7 nm. ZnO NC assembled films were fabricated on a glass substrate by deposition with the colloidal ZnO NCs dispersed in toluene. The film composed of the NCs showed good optical transparency in the visible to near-infrared region. A device coupling the ZnO NC film with a p-type Cu2 ZnSnS4 (CZTS) NC film exhibited an obvious diode-like current–voltage behavior. The results suggest that the transparent ZnO film has a potentiality to be used for an n-type window layer in some optoelectronic applications.